Sustainability in government finance - Chin, Aina Hui Li (Universiti Malaysia Sarawak (UNIMAS), 2013)
This research analyzes the linkage between economic growth and government expenditure and as well as the economic growth and government debt in Malaysia by taking account government development expenditure, government operating expenditure, domestic debt and external debt. This research is conducted based on the 32 observations for government expenditure and economic growth in Malaysia, which are from the year of 1978 to 2010. As for government debt and economic growth, the research is conducted based on the 22 observations from 1988 to 201 ~ The methods of unit root test, Johansen's co-integration test, Vector Error Correction Modeling (VECM) as well as the Granger causality test are used in this research to analyze the relationship between economic growth and government expenditure and also economic growth and government debt in Malaysia. The test of Johansen's cointegration indicates the existence of a long run linkage between economic growth and government expenditure and as well as the economic growth and government debt. In addition, empirical results reveal that causality does exist from economic growth towards governm,ent expenditure and domestic debt. Policymakers can adopt government expenditure especially development expenditure as policy tool to enhance economic growth.